2017
DOI: 10.1111/imre.12191
|View full text |Cite
|
Sign up to set email alerts
|

Does Size Really Matter? On the Relationship between Immigrant Group Size and Anti-Immigrant Prejudice

Abstract: Group threat theory understands prejudice as a manifestation of the threat, either actual or assumed, that minority groups pose to majority groups. This theory is often operationalized by analyzing the impact of group size on anti-immigrant prejudice. We test this hypothesis with a new dataset documenting 487 effects of group size on prejudice provided in 55 studies. More than half of these results show no relationship and the remainder shows both positive and negative relationships. Three explanations for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 79 publications
(163 reference statements)
4
47
0
Order By: Relevance
“…Meanwhile, this version of group threat theory has received limited support in Europe (Pottie‐Sherman & Wilkes ) and is at odds with previous Nordic comparisons using aggregate measures (Ervasti et al ). Another scenario, therefore, is the one suggested by intergroup contact theory (Hewstone & Swart ) that more immigrants leads to less opposition.…”
Section: The Country Contextsmentioning
confidence: 99%
“…Meanwhile, this version of group threat theory has received limited support in Europe (Pottie‐Sherman & Wilkes ) and is at odds with previous Nordic comparisons using aggregate measures (Ervasti et al ). Another scenario, therefore, is the one suggested by intergroup contact theory (Hewstone & Swart ) that more immigrants leads to less opposition.…”
Section: The Country Contextsmentioning
confidence: 99%
“…In doing so, many studies argue for the realistic account of group interests related to the group competition for limited resources that effectively determines public attitudes on immigration (Olzak, 1994;Quillian, 1995). However, given rather mixed evidence for the "group size" argument (Kustov, Laaker, & Reller, 2019;Pottie-Sherman & Wilkes, 2017), scholars have been compelled to develop a number of additional empirical tests that qualify the popular perception of economic group threat (Hainmueller & Hopkins, 2014;Meuleman, 2010). Most prominently, natives are expected to oppose immigrants who are perceived to be a net loss for the economy due to their characteristics (e.g., low-skilled).…”
Section: Perception Of Intergroup Economic Competitionmentioning
confidence: 99%
“…Making this distinction may be useful in future research. Furthermore, in their meta-study of the effect of out-group size on anti-immigrant sentiment, Pottie-Sherman and Wilkes (2015) found that perceived out-group size is more likely to have a positive effect on anti-immigrant sentiments than actual immigration. Hence, future research should consider including both actual and perceived (changes in) immigration in their models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%